Analisis Konstruksi Makna Kata Khasyyah Perspektif Al-Qur’an: (Sebuah Tinjauan Semantik Ensiklopedik) - Muhamad Khabib Imdad Muhamad Khabib Imdad (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo Indonesia, 2025)
The language of the Qur’an possesses a distinctive aesthetic through the lexical filtration of each fragment, wherein specific meanings and purposes are embedded and must be explored comprehensively. This study positions itself within that tradition by examining one of the frequently recurring terms in the Qur’an, khasyyah. This word is often interpreted as